2017
DOI: 10.3390/w9010069
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory of Omnivorous Fish Shapes the Food Web Structure of a Chinese Tropical Eutrophic Lake: Evidence from Stable Isotope and Fish Gut Content Analyses

Abstract: Studies suggest that, unlike the situation in temperate lakes, high biomasses of omnivorous fish are maintained in subtropical and tropical lakes when they shift from a turbid phytoplankton-dominated state to a clear water macrophyte-dominated state, and the predation pressure on large-bodied zooplankton therefore remains high. Whether this reflects a higher degree of herbivory in warm lakes than in temperate lakes is debatable. We combined food web studies using stable isotopes with gut content analyses of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 69 publications
(112 reference statements)
3
5
0
Order By: Relevance
“…Comparisons of SIA values from our study and other studies (Table 3) indicate that TMG in Wales generally have higher δ 13 C and δ 15 N values (i.e., more enriched) than those reported in another study in Great Britain (Britton et al, 2010), indicating a higher trophic level (δ 15 N) and a different primary source of carbon (δ 13 C). Our δ 13 C values are relatively high and closer to the ones reported in China -where topmouth gudgeon is a native species (Mao et al, 2012(Mao et al, , 2016Gao et al, 2017) than to values observed in Belgium where the species is invasive (Tran et al, 2015). High δ 13 C values are more typical of benthic food pathways, compared to pelagic food pathways which tend to be more 13 C depleted (Pinnegar and Polunin, 1999).…”
Section: Discussionsupporting
confidence: 78%
“…Comparisons of SIA values from our study and other studies (Table 3) indicate that TMG in Wales generally have higher δ 13 C and δ 15 N values (i.e., more enriched) than those reported in another study in Great Britain (Britton et al, 2010), indicating a higher trophic level (δ 15 N) and a different primary source of carbon (δ 13 C). Our δ 13 C values are relatively high and closer to the ones reported in China -where topmouth gudgeon is a native species (Mao et al, 2012(Mao et al, , 2016Gao et al, 2017) than to values observed in Belgium where the species is invasive (Tran et al, 2015). High δ 13 C values are more typical of benthic food pathways, compared to pelagic food pathways which tend to be more 13 C depleted (Pinnegar and Polunin, 1999).…”
Section: Discussionsupporting
confidence: 78%
“…Comparisons of SIA values from our study and other studies (Table 3) indicate that TMG in Wales generally have higher δ 13 C and δ 15 N values (i.e more enriched) than those reported in another study in Great Britain (Britton et al 2010), indicating a higher trophic level (δ 15 N) and a different primary source of carbon (δ 13 C). Our δ 13C values are relatively high and closer to the ones reported in China -where topmouth gudgeon is a native species (Gao et al 2017;Mao et al 2012;Mao et al 2016) than to values observed in Belgium where the species is invasive (Tran et al 2015). High δ 13 C values are more typical of benthic food pathways, compared to pelagic food pathways which tend to be more 13 C depleted (Pinnegar, Polunin 1999).…”
supporting
confidence: 78%
“…We, therefore, suggested that the seasonal differences in δ¹³C values of pelagic source were explained by pH, composition of algae and contribution of terrestrially derived organic matter based on higher turbidity. Pelagic source (seston) from Lake Zinav were more ¹³C depleted compared with previously measured values from rivers and dam lakes of Central Black Sea region where this current study was performed (Akin et al, 2010;Kaymaket al, 2015), and those from other eutrophic lakes (Zhou et al, 2011;Mao et al, 2012;Gao, Zhong, Ning, Liu &Jeppesen, 2017). This might be suggested that carbon derived from microbial loop by bacterioplankton in water column of Lake Zinav, such as nitrification (Kelley & Coffin, 1998), sulfur (Doi et al, 2006 and methane oxidation (Jones & Grey, 2011).…”
Section: Discussionsupporting
confidence: 56%